Climate-smart agriculture measurement, reporting and verification in the Republic of Zimbabwe - World Agroforestry Centre; Unique Forestry and Land Use (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The Republic of Zimbabwe recognizes the need to take action to harmonize agricultural development with environmental protection and to reduce vulnerability to climate change. At least 22 unique projects and policies relevant to CSA were underway in 2014, and more have started since then (figure 1). Outcomes from CSA projects, however, have not yet been tracked or reported on in a coordinated or comprehensive way. Indeed, measurement, reporting and verification (MRV) is barely considered in seminal documents such as the recently released Zimbabwe CSA Manual. As a result, the contributions of CSA projects, programmes and policies toward national development and climate goals are not accounted for, and CSA is not explicitly integrated into budgetary processes.